New Results on Soft Spectral in Soft Banach Algebra - F. Al-Mayahi, Noori; K. Mohammed, Hayder (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2018)
In this paper, concepts of soft character, soft division algebra, soft ideal, soft maximal ideals are introduced .Soft Spectral Radius Formula are introduced and proved, some properties of Soft gelfand algebra are proved.